UPAYA PENCEGAHAN STUNTING MELALUI PEMANFAATAN DAUN KELOR PADA MASYARAKAT DI DESA LANGGE KECAMATAN TAPA KABUPATEN BONE BOLANGO - Rahmatiah, Rahmatiah; Wiroto, Dondick Wicaksono; Tui, Fenti Prihatini; Hariana, Hariana (Nindikayla Institute, 2023)
Stunting is still a health problem in Indonesia which is spread across all regions including Gorontalo Province. Langge Village has people who are indicated to be stunted at the age of two years to five years, even though access to information, including health information, is very easy because this village is located not far from the capital city of Gorontalo and the capital city of Bone Bolango Regency. One effort to reduce the increasing number of stunting in Langge Village is through the use of Moringa leaves as a raw material which is processed into nutritious food and drinks to be consumed by pregnant women and toddlers so that fetuses and children are suitable for ideal growth and development. The availability of abundant raw materials in an area does not guarantee that the community is free from stunting, so education is needed for the community to understand preventive efforts as appropriate and effective steps to prevent stunting. The results of processing Moringa leaves are Moringa Pudding and Moringa leaf powder which can be mixed into drinking water, milk and food consumed by children under five, pregnant women and the elderly as well as the general public.